Production of water-soluble few-layer graphene mesosheets by dry milling with hydrophobic drug - Rubio, Noelia (Langmuir : the ACS journal of surfaces and colloids, 2014)
A novel, fast, and easy mechano-chemistry-based (dry milling) method has been developed to exfoliate graphene with hydrophobic drugs generating few-layer graphene mesosheets (< 10 nm in thickness and ∼1 μm in width). The electronic properties of the graphitic structure were partially preserved after the milling treatment compared with graphene oxide prepared by Hummers' method. Several characterization techniques such as thermogravimetric analysis, Raman spectroscopy, atomic force microscopy, electron microscopy, and molecular dynamics simulation were used to characterize this material. The drug-exfoliated mesosheets were pharmacologically inactive, offering a new approach for making water-soluble few-layer graphene mesosheets upon dry milling with hydrophobic drugs, mainly used as exfoliating agents